(3bSWGS GdCacGQ aj JMbjb GdCSQGQs - (3eMeO Hf eMehO Hf eMeO Hf CMeO, TeS GdOjf GdSeQbfOj,J (B780 (3g` s ((3CSYO Hf CHj HcQ s)
(3ChdgG (B:s
(3hLYdJg GdhGM GdefWb hGdeHGOF hGdeSGFd s
(3BNQgG (B:s
(3Hd LejY GdUGMHI YfO Gddg hQShdg hdGjLhR GdWYf ajge s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B4s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs